Inheems Rechts gemeenschap Self-Government as a Means of Implementing Customary Law (Studies on Baduy Customary Law Community Units) - Arif Nugroho; Jumanah Jumanah (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
This article discusses Self-Government of Inheems Rechtsgemeen schap/Customary Law Community Units (KMHA) as a means of implementing customary law. It is known that there is a bias in the understanding of the meaning of KMHA in the 1945 Constitution Article 18B Paragraph 2 and in practice it is mixed up with the meaning of Village, Traditional Village and Indigenous Peoples, this is due to bias in the regulation of Law 6/2014. The representatives of the Baduy Indigenous People at the Seba Baduy event expressed their aspirations for the Baduy KMHA to be recognized by Regional Regulations (Perda). The language conveyed is that their Traditional Village (Baduy) does not yet have a legal umbrella as a legal force for the community. The Lebak Regency Government has responded positively to this aspiration. Based on that, this article wants to examine the concept of KMHA, so that it can be clearly identified what the characteristics of KMHA actually are. In this study the method used was descriptive with a qualitative approach. The results revealed that the Baduy KMHA turned out to have characteristics similar to those of KMHA (Inheems Rechtsgemeenschap or Adat Rechtsgemeenschap) referred to by Van Vollenhoven (1907). If so far we have seen the construction of Law 6/2014 and the response from the district government to facilitate local regulations, this indicates that both the Central and Regional Governments (Lebak) do not really understand the juridical and theoretical concepts regarding KMHA, villages and traditional villages and where the differences are, so the steps taken to recognize and treat KMHA is not according to the principle (according to the constitutional). It is hoped that all State Organizers must understand correctly and correctly the concept of KMHA both constitutionally and in theory so that the steps are right in recognizing and treating KMHA which are self-governing by customary law.